Validity and reliability of the VmaxPro IMU for back squat exercise in multipower machine - Olaya-Cuartero, J.; Villalon-Gasch, L.; Penichet-Tomas, A.; Jimenez Olmedo, J. M. (Journal of Physical Education and Sport, 2022)
Currently, the application for velocity-based training through a 3D Motion Capture System is discarded due to the economic and personal resources involved, being used mainly as laboratory instruments. As an alternative, different device on the market make it possible to assess and control training loads, although not all use the same technology to measure execution velocity. Approach: Specifically, the inertial measurement unit VmaxPro is one of the new additions to the market of sensors based on accelerometry for the control of execution velocity in resistance training and the reliability and validity of this type of device need to be analysed. Purpose: Thus, this study aimed to conduct a concurrent validation for the velocity and range of displacement of the barbell of VmaxPro against a 3D Motion Capture System as the gold standard. The secondary purposes of this study were to analyse the reliability and measurement errors (both random and systematic) of VmaxPro. Results: The main results of the present study are shown in terms of reliability, validity, and accuracy of the VmaxPro. Firstly, the practical device shows excellent to good ICCs values for the reliability of the velocity and range of displacement of the barbell, respectively. Secondly, VmaxPro presents a small underestimation of the velocity of its systematic error (-0.021 m/s) in comparison to the 3D Motion Capture System, contrary to the random error (0.053 m/s), overestimating the velocity measurement, and a measurement errors both systematic and random close to 2 cm for the range of barbell displacement. Finally, VmaxPro presents valid values for both the velocity and range of displacement of the barbell, being a suitable instrument for this purpose. Conclusions: It would be possible for both coaches and athletes to use the inertial measurement unit VmaxPro for the control, monitoring, and evaluation of strength training.